An Analysis of the Factors that Encourage Students to Participate in the Student Exchange Program at Buana Perjuangan University, Karawang - Yeni Fajrin; Muhammad Adhimawan Wijaya; Neni Sumarni (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Student mobility through student exchange programs plays a vital role in enhancing the quality of higher education, yet participation among students from non-metropolitan universities remains relatively low. This study aims to analyze the motivational factors that encourage students at Buana Perjuangan University Karawang to participate in the student exchange program within the framework of the Merdeka Belajar Kampus Merdeka (MBKM) policy. Five variables were examined: academic experience, skill enhancement, career opportunities, personal development, and cultural exchange. Using a quantitative approach, data were collected from 140 students through an online questionnaire and analyzed with Exploratory Factor Analysis (EFA) using SPSS 21. The findings reveal that all five variables converge into a single dominant construct, with a KMO value of 0.903, factor loadings above 0.80, and variance explained of 78.64%. This finding highlights that students’ motivation in non-metropolitan contexts tends to be holistic rather than fragmented, distinguishing it from prior studies conducted in metropolitan settings. The results provide new insights into the integrated nature of student motivation and offer practical implications for universities in formulating strategies to enhance participation in the student exchange program.